Freedom of testation and freedom of choice of the law applicable to the succession - Fontanellas Morell, Josep María (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Among the features of Regulation 650/2012, on cross-border successions, the introduction of the testator’s choice of the succession law stands out. In order to justify the institution and its inclusion in the European instrument, it is easy to imagine a kind of natural correlation between the freedom of testation, granted by national law, and the possibility to select the applicable law which is characteristic of international inheritances. Nevertheless, scholars tend to invoke the security and predictability that professio juris provides in the estate planning. Yet resolutions stemming from Directorate General for Registries and Notary Affairs are based more on the freedom of testation than on legal certainty.
Keywords: succession upon death; freedom of testation; cross-border successions; choice of law; tacit choice of law; legal certainty